Amerikanische Malerei 1930 - 1980. - Armstrong, T. (München : Prestel Verlag, 1981)
Albers, Josef ; Albright, Ivan Le Lorraine ; Ault, George C. ; Avery, Milton ; Bailey, William ; Bartlett, Jennifer ; Baziotes, William ; Beal, Jack ; Beckman, William ; Benton, Thomas Hart ; Berman, Eugene ; Biederman, Charles ; Bischoff, Elmer ; Bluemner, Oscar Julius ; Bolotowsky, Ilya ; Brooks, James ; Brown, Roger ; Browne, Byron ; Burchfield, Charles ; Close, Chuck ; Crawford, Ralston ; Curry, John Steuart ; Davis, Stuart ; Diebenkorn, Richard ; Diller, Burgoyne ; Dine, Jim ; Dove, Arthur G. ; Downes, Rackstraw ; Estes, Richard ; Ferren, John ; Francis, Sam ; Frankenthaler, Helen ; French, Jared ; Gallatin, Albert Eugene ; Gillespie, Gregory ; Glarner, Fritz ; Goings, Ralph ; Gorky, Arshile ; Gottlieb, Adolph ; Graham, John D. ; Guglielmi, O. Louis ; Guston, Philip ; Hartley, Marsden ; Held, Al ; Hirshfield, Morris ; Hofmann, Hans ; Hogue, Alexandre ; Holty, Carl ; Hopper, Edward ; Irwin, Robert ; Jensen, Alfred ; Johns, Jasper ; Katz, Alex ; Kelly, Ellsworth ; Kline, Franz ; de Kooning, Willem ; Krasner, Lee ; Kuhn, Walt ; Kuniyoshi, Yasuo ; Leslie, Alfred ; Levine, Jack ; Lichtenstein, Roy ; Lindner, Richard ; Louis, Morris ; Lundeberg, Helen ; Marca-Relli, Conrad ; Marden, Brice ; Marin, John ; Marsh, Reginald ; Martin, Agnes ; Matulka, Jan ; Maurer, Alfred ; Miller, Kenneth Hayes ; Mitchell, Joan ; Morris, George L.K. ; Motherwell, Robert ; Müller, Jan ; Murch, Walter Tandy ; Murray, Elizabeth ; Neel, Alice ; Newman, Barnett ; Noland, Kenneth ; Nutt, Jim ; O'Keeffe, Georgia ; Olitski, Jules ; Ossorio, Alfonso ; Park, David ; Paschke, Ed ; Pearlstein, Philip ; Pereira, Irene Rice ; Pollock, Jackson ; Porter, Fairfield ; Pousette-Dart, Richard ; Rauschenberg, Robert ; Reinhardt, Ad ; Rivers, Larry ; Rosenquist, James ; Rothko, Mark ; Ruscha, Edward ; etc.
boek